'I guess' to 'I get': an effective use of smart technology to transform undergraduate statistics education. (24th January 2013) - Han, Bo; Prybutok, Victor R.
With the prominence of mathematics, statistics is playing an increasingly important role in an undergraduate student's academic and professional careers. Numerous studies have found that a large number of students are fearful of taking statistics classes because of the subject's complexity. Several emerging technologies, including the most recent smart mobile technology, were adopted to assist students with learning. In the current study, we propose a pedagogical innovation to the standard format of statistics homework assignments, which are one of the most important components in developing a student's critical thinking abilities. We then offer a corresponding solution of effective use of smart technology to implement the new pedagogy. Analysis of the student feedback provided insights for the future research on how to use smart technology to effectively improve undergraduate statistics education.